Vulnerability assessment in Lefkada old town (W. Greece) with the use of EMS-98; comparison with the 14-8-2003, Mw= 6.2, earthquake effects. First results. - Kalantoni, D.; Pomonis, A.; Kassaras, I.; V. Kouskouna; K. Pavlou; Vassilopoulou, S.; Karababa, F.; Makropoulos, K. (Vienna Congress on Recent Advances in Earthquake Engineering and Structural Dynamics (VEESD 2013), 2013)
The purpose of this paper is to assess the vulnerability to ground shaking of the building stock in the old town of Lefkada Island (Ionian Sea, W. Greece). The study area lies in the most seismically active zone of Greece region. Most of its buildings were built with local practices and have been designated by the European Council Cultural Heritage Unit as representative earthquake resistant constructions. Within the context of this research we conducted an in-situ survey, of all buildings in the old town. In addition, the 2001 buildings census catalogue elaborated by the National Statistical Service of Greece was employed, as well as the damage inspection data following the 2003 earthquake. The collected data, after a detailed processing, were projected as they would have been prior to the August, 14, 2003, Mw=6.2 Lefkada earthquake. Each building was indexed by an EMS-98 vulnerability class. All results were combined in an ArcGIS scheme in order to compute the lateral vulnerability distribution and to compare it with the 14/8/2003 earthquake effects.